MODEL PHYSICAL EDUCATION LESSON PLAN ON DEVELOPMENT OF STRENGTH OF DEXTEROUS AMOUNG PREADOLOCENTS - AJAZ AHMAD DAR; Prof. SUNIL KUMAR; Dr.S.VIJAY; SAJAD AHMAD DAR (RADJA PUBLIKA, 2023)
Abstract The purpose of the study was to adaptation of model physical education lesson plan on development of strength of dexterous among preadolescents. To achieve the purpose 40 right handed school girls from Anantnag district, Jammu and Kashmir, India where selected as subject at random and there age ranged between 10-13 years .The subjects were divided into two groups namely physical training group (n=20) and control group (n=20) .The physical training group underwent training for 45 min/3 days /8 weeks including warming up and cooling down exercises. The strength was taken as dependent variable and was tested by hand grip dynamometer before and after the experimental period for both groups on right and left hand alternatively. The collected data was analyzed by using ANCOVA to find significance between groups. Further, the independent‘t’ was employed to find out the difference between left and right hand improvement on selected dependent variable and magnitude of improvement was calculated to find the level of improvement on dexterous. The level of confidence was fixed at 0.05. Hence it was concluded that The model physical education lesson plan improves the strength of dexterous both (Right and Left hand) as compared to the control group.